Hyaladherins May be Implicated in Alcohol-Induced Susceptibility to Bacterial Pneumonia - Crotty, Kathryn M.; Yeligar, Samantha M. (Frontiers in Immunology, 2022)
Although the epidemiology of bacterial pneumonia and excessive alcohol use is well established, the mechanisms by which alcohol induces risk of pneumonia are less clear. Patterns of alcohol misuse, termed alcohol use disorders (AUD), affect about 15 million people in the United States. Compared to otherwise healthy individuals, AUD increase the risk of respiratory infections and acute respiratory distress syndrome (ARDS) by 2-4-fold. Levels and fragmentation of hyaluronic acid (HA), an extracellular glycosaminoglycan of variable molecular weight, are increased in chronic respiratory diseases, including ARDS. HA is largely involved in immune-assisted wound repair and cell migration. Levels of fragmented, low molecular weight HA are increased during inflammation and decrease concomitant with leukocyte levels following injury. In chronic respiratory diseases, levels of fragmented HA and leukocytes remain elevated, inflammation persists, and respiratory infections are not cleared efficiently, suggesting a possible pathological mechanism for prolonged bacterial pneumonia. However, the role of HA in alcohol-induced immune dysfunction is largely unknown. This mini literature review provides insights into understanding the role of HA signaling in host immune defense following excessive alcohol use. Potential therapeutic strategies to mitigate alcohol-induced immune suppression in bacterial pneumonia and HA dysregulation are also discussed.